2020
DOI: 10.1002/ange.202002627
|View full text |Cite
|
Sign up to set email alerts
|

Micromanipulation of Mechanically Compliant Organic Single‐Crystal Optical Microwaveguides

Abstract: Flexible organic single crystals are evolving as new materials for optical waveguides that can be used for transfer of information in organic optoelectronic microcircuits.I ntegration in microelectronics of such crystalline waveguides requires downsizing and precise spatial control over their shape and sizea tt he microscale,h owever that currently is not possible due to difficulties with manipulation of these small, brittle objects that are prone to cracking and disintegration. Here we demonstrate that atomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…10 In 2012, Reddy and coworkers reported a kind of organic co-crystal that exhibited elastic bending ability under applied stress. 11 Subsequently, elastic and plastic organic crystals have been rapidly developed and deeply studied by Desiraju 12,13 , Naumov [14][15][16] , Reddy 17.18 , Hayashi 19,20 , Chandrasekar 21, 22 and our group [23][24][25][26][27][28] Notably, flexible organic crystals compatible with optical and electrical functions have been reported recently, which advanced the application of these flexible materials in optoelectronics. [29][30][31] There are two key limiting factors in expanding the application of flexible organic crystals: single mechanical property and narrow applicable temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…10 In 2012, Reddy and coworkers reported a kind of organic co-crystal that exhibited elastic bending ability under applied stress. 11 Subsequently, elastic and plastic organic crystals have been rapidly developed and deeply studied by Desiraju 12,13 , Naumov [14][15][16] , Reddy 17.18 , Hayashi 19,20 , Chandrasekar 21, 22 and our group [23][24][25][26][27][28] Notably, flexible organic crystals compatible with optical and electrical functions have been reported recently, which advanced the application of these flexible materials in optoelectronics. [29][30][31] There are two key limiting factors in expanding the application of flexible organic crystals: single mechanical property and narrow applicable temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Theu se of flexible-crystal waveguides in photonic microcircuits is limited by the lack of suitable manipulation techniques to deform microcrystals into intricate shapes. Furthermore,the implementation of mechanical operation in microcrystals is rather tricky due to their soft and fragile nature.M icromanipulation with atomic-force-microscopy (AFM) cantilever tips has turned out to be ap romising technique [11] to mechanically shape microcrystals without causing damage to them.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the investigation of elastic organic crystals is one of the currently developing trends in flexible photonics. Elastic organic crystals under the external stimuli usually have various outstanding mechanical behaviors, e.g., bending [37,38,[82][83][84][85] and twisting [86,87]. As a pioneer work, Prof. Zhang et al firstly demonstrated the flexible microrods of (E)-1-(4-(dimethylamino)phenyl)iminomethyl-2-hydroxyl-naphthalene (DPIN) crystals (Fig.…”
Section: D Flexible Optical Waveguidesmentioning
confidence: 99%